Do Technology Utilization and Lecturer Competence Matter for Online Learning? The Mediating Role of Independent Learning - Ratieh Widhiastuti; Wisudani Rahmaningtyas; Nina Farliana; Indrawati Indrawati (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2022)
This study examines the effect of technology utilization and lecturer competence on the effectiveness of online learning with independent learning as a mediating variable. The population in this study were students of Economics Education Department, Universitas Negeri Semarang in class of 2018. The sampling technique involved in this study is a saturated which consisting of 120 students. The data further analyzed using descriptive statistical and path analysis. The results showed that technology utilization had no effect on the effectiveness of online learning for computer courses. Lecturer competence and learning independence had a positive and significant effect on the effectiveness of online learning for computer courses. The technology utilization had no effect on learning independence, while lecturer competence positively impacts on learning independence. Additionally, independent learning failed in mediating the effect of technology utilization but it can mediate the effect of lecturer competence on the effectiveness of online learning. From these findings, lecturers should provide more interesting learning materials so that the effectiveness of online learning increases and can foster independent learning in students. Keywords: Effectiveness of online learning, Learning independence, Lecturer competence, Technology utilization